Geopolitical Dimensions of Russia’s Control over the Peanut Hole in the Okhotsk Sea: Sovereignty and the Challenges of International Maritime Law - Muhammad Ridha Iswardhana (IHSA Institute, 2026)
This research explores Russia’s geopolitical strategy in asserting control over the Peanut Hole in the Sea of Okhotsk, a strategically significant maritime area enclosed by Russia's Exclusive Economic Zone (EEZ). The research addresses the tension between Russia's sovereignty claims and international maritime law, particularly the United Nations Convention on the Law of the Sea (UNCLOS). This research examines the legal complexities and geopolitical implications of Russia's policy to extend its jurisdiction beyond the 200-nautical-mile limit, asserting exclusive rights over seabed resources while the waters above remain classified as high seas. The analysis critically evaluates Russia's motivations, including economic interests in vital resources like fish, oil, and gas, and the broader implications for global maritime governance. The study concludes that Russia's actions, while legally contentious, reflect a strategic effort to enhance its economic resilience and military influence in the region. This case studies found the evolving challenges in reconciling national sovereignty with international legal frameworks, offering valuable insights into maritime resource management and geopolitical power dynamics in the Asia-Pacific region